Canadian State Trials. - Wright, Barry, 1957-; Binnie, Susan W. S. (Susan Wendy Strickland), 1941-; Tucker, Eric, 1951- (University of Toronto Press, 2022)
The final volume of the Osgoode Society's Canadian State Trials series sheds light on the legal issues surrounding perceived security threats in Canada in the twentieth century.